1980
DOI: 10.1159/000131429
|View full text |Cite
|
Sign up to set email alerts
|

The unusual karyotype of the lesser kudu, <i>Tragelaphus imberbi</i><i>s</i>

Abstract: The chromosome set of the lesser kudu, Tragelaphus imberbis, consists of 38 elements in both sexes. In contrast to most other members of the bovid subfamily Tragelaphinae, both the X and the Y chromosomes are compound, having fused with identical autosomes from ancestors presumed to have higher chromosome numbers. From a comparison of the unusual sex chromosomal rearrangements that have occurred in this family, a hypothetical lineage has been derived. This family tree and the details of various banding studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This is actually a neo-X believed to have been formed by centric fusion between the original X and the homolog of cow chromosome 13. Benirschke et al (1980) identified a similar and potentially homologous heterochromatic region on the acrocentric presumed neo-Y [likely a t(13;Y)] of the lesser kudu, but we have not yet analyzed this compound chromosome. Of further interest is the Y chromosome of nilgai.…”
Section: Karyotypic Evolution and The Chromosomal Distribution Of Satmentioning
confidence: 99%
“…This is actually a neo-X believed to have been formed by centric fusion between the original X and the homolog of cow chromosome 13. Benirschke et al (1980) identified a similar and potentially homologous heterochromatic region on the acrocentric presumed neo-Y [likely a t(13;Y)] of the lesser kudu, but we have not yet analyzed this compound chromosome. Of further interest is the Y chromosome of nilgai.…”
Section: Karyotypic Evolution and The Chromosomal Distribution Of Satmentioning
confidence: 99%